An experimental comparison of participants’ experience in face-to-face, video, and virtual reality meetings - van Gent, Sophie; Langefeld, Anja; Held, Niels; Cremers, Anita; Loots, Gjalt; Gunkel, Simon N. B. (Frontiers in Virtual Reality, 2024)
The increasing prevalence of remote working and the challenges it presents underscores the need for alternative technologies that can provide a more healthy, natural and social remote meeting experience. However, there is a limited understanding of how such technologies compare to other modalities, especially face-to-face communication. This study investigates the impact of three meeting modalities -face-to-face, videoconferencing, and virtual reality (VR) -on participants' experience of social presence, well-being, and task engagement during a meeting involving a negotiation task. Despite the hypothesis that these experiences would significantly differ across modalities, no such differences were found. We suspect that characteristics of the meeting participants and the negotiation task, the meeting duration, as well as the measurements used have moderated the effect of meeting modality on experience. The VR modality was however perceived as more enjoyable, suggesting that immersive technologies like VR hold potential for enhancing the remote meeting experience. The results also underscore that there is no one-size fits all solution when it comes to choosing the best meeting modality. The study stresses the need for ongoing research to optimize the remote meeting experience in the context of different meeting objectives and practical considerations.